Annual survival probabilities of anadromous arctic char remain high and stable despite interannual differences in sea ice melt date - Caza-Allard, Isabeau; Mazerolle, Marc J.; Harris, Les N.; Malley, Brendan K.; Tallman, Ross F.; Fisk, Aaron T.; Moore, Jean Sébastien (Arctic Science, 2021)
Throughout their range, anadromous Arctic Char (Salvelinus alpinus (Linnaeus, 1758)) support commercial, recreational, and subsistence fisheries that are important economically, socially, and culturally. However, drivers of interannual variation in survival in this species remain poorly understood. Here, we aimed to quantify the impact of environmental and biological parameters on the survival probability of anadromous Arctic Char near the community of Cambridge Bay, Nunavut, Canada. To do so, we tracked 183 Arctic Char tagged with acoustic transmitters and used capture–mark–recapture methods to estimate survival probabilities over six years. Annual survival probabilities for individuals was high, varying between 0.79 and 0.88, whereas recapture probabilities varied between 0.64 and 0.90. Interannual variation in survival probability was low and neither the environmental (air temperature and sea ice cover) nor biological (sex) variables influenced survival probability. These estimates suggest that annual survival probability is high for anadromous adult Arctic Char in the Cambridge Bay area, despite clear differences in the ice cover melt date among years. These results further our understanding of the demographic parameters of Arctic Char in the region, which will be important for future assessments of the sustainability of commercial fisheries as well as for predicting population responses to a rapidly changing Arctic.